Reforma educativa em Angola: a monodocência no ensino primário em Cabinda - Ndombele Mayembe (2017)
Through this tool we analyse the impact of educational reform in Angola, particularly in Cabinda, looking forward to understand and describe the teaching practices in the context of the extension of a single teacher. This is an exploratory research that makes use of document analysis, questionnaires, school assistance and conducting interviews for understanding the changes in the educational system. Seeks to identify the opinions of teachers on their performance in the new disciplines and also on educational reform. It also looks to know how teachers are reacting to this process of change both inside and outside the classroom and what are the views of society on the new system of education. These issues were accordingly discussed on the basis of studies and research on educational policies, initial and continuing teacher training, teacher training models, professionalization, teaching activity, educational reforms and teachers' working conditions. In relation to the single teacher also used up real situations of combined teaching with the views of the national press and the observation in the classroom. The survey results illustrated that teachers were not brought into the scenario about the change of the educational system; not participated in training who worked new content that were not part of their training; They do not agree with the educational reform, with a single teacher, with automatic approval and have difficulty in teaching new content. To teach new courses, some teachers rely on colleagues and consult books, hands outs while others put them in the background. The results also indicate that the initial and continuing training is in step with the changes introduced by the reform, working conditions are poor, and there is an intensification of teaching. The results also revealed that many teachers who teach in primary education have low levels of education and others continue to work the same way they were working in the old system.